2019
DOI: 10.1186/s12903-019-0819-0
|View full text |Cite
|
Sign up to set email alerts
|

Dental health status and oral health behaviours of patients with facial burn in Pakistan

Abstract: Background There is a limited understanding about the oral health of patients with facial burn, hence the aim was to describe the oral health status and the related risks factors. Methods This cross-sectional study had randomly and systematically recruited facial burn patients from the Burn Care Center, Pakistan Institute of Medical Sciences, Islamabad, from June of 2016 to July of 2017. Intraoral examination recorded the DMFT, CPI and OHI-S. Information on the socio-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 42 publications
3
21
0
Order By: Relevance
“…Evidence has also linked these conditions to less frequent tooth brushing and fewer dental visits [11]. Poor oral health outcomes in individuals with facial burns have been linked to dental anxiety [12]. However, there is little discussion on the influence of psychosocial factors on oral health in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has also linked these conditions to less frequent tooth brushing and fewer dental visits [11]. Poor oral health outcomes in individuals with facial burns have been linked to dental anxiety [12]. However, there is little discussion on the influence of psychosocial factors on oral health in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the participants avoided the dentist for fear of treatment and feeling embarrassed with their dental conditions. Those with social barriers have problems to interact with other people because they are shy, lack self-confidence or have low esteem (28); which could be due to the dental condition and/or disfigured appearance. Thus, they lose the opportunity to learn about good oral hygiene practice and get the treatment for their condition.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study should be interpreted with caution. Several limitations relating to the limited inference from the cross-sectional study design, reference population from a single institution in Pakistan, lack of reliability study due to patients unwilling to return for clinical reassessment and recall bias, have been discussed earlier (28). A very limited inference can be drawn for facial burn patients who are not followed-up at a burn centre.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A local study showed that only 10.7% of the adult population had visited dentists for regular checkups during the last year in Pakistan. 6 Hence, easy access to oral healthcare facilities with affordability and addressing the barriers to this basic human right is of great importance for the overall well-being of the adult population. There is limited availability of public dental healthcare facilities serving oral health care needs as the dentist to population ratio is 1:1305811 in Pakistan.…”
Section: Introductionmentioning
confidence: 99%